Evaluation of stable reference genes in white mustard (Sinapis alba) for qRT-PCR analysis under various stress conditions - DIXIT, SHIKHA; JANGID, VINOD KUMAR; GROVER, ANITA (The Indian Journal of Agricultural Sciences, 2020)
White mustard (Sinapis alba L.) is a member of Brassicaceae family and is a source of various biotics stress resistance genes. S. alba is closely related to the cultivated Brassica juncea which exhibit susceptibility towards various pathogens. Quantitative real-time PCR (qRT-PCR) is an efficient method to estimate the gene expression levels but the efficiency of its outcome is largely influenced by the stability of the reference gene. Many studies have reported considerable variation in the expression of reference genes in different tissues and treatments therefore, screening for accurate reference genes is important for functional analysis of the target gene. This study was conducted with the aim of identifying suitable reference genes for efficient quantitative gene expression analysis in S. alba. This experiment was conducted in National Phytotron Facility, IARI, Pusa campus in the month of November-December 2017. In this study, stability of seven candidate reference genes were identified across diverse samples of S. alba representing- hormone treated, wounded and A. brassicae inoculated samples. Results revealed that TIPS41 and PP2A the overall best performing reference genes in S. alba. However, best-ranked reference gene should be selected according to the specific sample subset.